CPI Aggregation: A New Weighting Scheme - Rahman, A.F.M. Ataur; Uddin, Noor Md. Wasi (Asian Business Review, 2012)
Consumer Price Index (CPI) of a particular region is primarily calculated through aggregation of individual household observations. This aggregation is done following two schemes, plutocratic and democratic. While both of them are useful for certain purposes, none of them actually give proper attention to poor households. In this study, we have shown that weighting scheme with certain mathematical characteristics can actually produce CPI, which can represent poor households better and thus can be more useful for development-oriented policymaking.